Drip groove on 4F roof (RFA-502_Rev A) - WOHA Designs PTE LTD; BUCG-ABC Joint Venture; Web Structures (2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of only PDF version of drawings.